International Migration and Development - Hanson, Gordon H. (World Bank, Washington, DC, 2017)
A decade ago, trade and investment liberalization dominated the global economic policy agenda. The World Trade Organization (WTO) had recently been created, the United States, Mexico and Canada were implementing North American Free Trade Agreement (NAFTA), and much of Southeast Asia and South America were near the peak of an economic boom that was driven in part by greater openness to inflows of foreign capital. In bilateral and multilateral discussions of economic integration, global migration was often missing from the docket entirely. The growth in labor flows from low-income to high-income countries has not been greeted with universal enthusiasm, either by policy makers or academics. In theory, international migration increases economic efficiency by shifting labor from low-productivity to high-productivity environments. As workers move from Central America to the United States, North Africa to Europe, or Southeast Asia to Australia, the global labor supply shifts from labor abundant to labor-scarce economies, compressing international differences in factor prices and raising global gross domestic product (GDP). Migrants enjoy large income gains family members at home share in these gains through remittances, and non-migrating workers in the sending country enjoy higher wages thanks to a drop in local labor supply (Aydemir and Borjas, 2007).